Pleural Effusions Following Liver Transplantation: A Single-Center Experience. (August 2021) - Lui, Justin K.; Spaho, Lidia; Hakimian, Shahrad; Devine, Michael; Bui, Rosa; Touray, Sunkaru; Holzwanger, Erik; Patel, Boskey; Ellis, Daniel; Fridlyand, Svetlana; Ogunsua, Adedotun A.; Mahboub, Paria; et al.
Introduction: This was a single-center retrospective study to evaluate incidence, prognosis, and risk factors in patients with postoperative pleural effusions, a common pulmonary complication following liver transplantation. Methods: A retrospective review was performed on 374 liver transplantation cases through a database within the timeframe of January 1, 2009 through December 31, 2015. Demographics, pulmonary and cardiac function testing, laboratory studies, intraoperative transfusion/infusion volumes, postoperative management, and outcomes were analyzed. Results: In the immediate postoperative period, 189 (50.5%) developed pleural effusions following liver transplantation of which 145 (76.7%) resolved within 3 months. Those who developed pleural effusions demonstrated a lower fibrinogen (149.6 ± 66.3 mg/dL vs 178.4 ± 87.3 mg/dL; P = .009), total protein (5.8 ± 1.0 mg/dL vs 6.1 ± 1.2 mg/dL; P = .04), and hemoglobin (9.8 ± 1.8 mg/dL vs 10.3 ± 1.9 mg/dL; P = .004). There was not a statistically significant difference in 1-year all-cause mortality and in-hospital mortality between liver transplant recipients with and without pleural effusions. Liver transplant recipients who developed pleural effusions had a longer hospital length of stay (16.4 ± 10.9 days vs 14.0 ± 16.5 days; P = .1), but the differences were not statistically significant. However, there was a significant difference in tracheostomy rates (11.6% vs 5.4%; P = .03) in recipients who developed pleural effusions compared to recipients who did not. Conclusions: In summary, pleural effusions are common after liver transplantation and are associated with increased morbidity. Pre- and intraoperative risk factors can offer both predictive and prognostic value for post-transplantation pleural effusions. Further prospective studies will be needed to further evaluate the relevance of these findings to limit instances of postoperative pleural effusions.